Effect of tDCS combined with virtual reality for post-stroke cognitive impairment: a randomized controlled trial study protocol - Cheng, Xiao-Ping; Wang, Zhao-Di; Zhou, Yue-Zhu; Zhan, Li-Qiong; Wu, Di; Xie, Li-Li; Luo, Kai-Liang; He, Jin-Peng; Lin, Wei; Ni, Jun; Lv, Lan; Chen, Xin-Yuan (BMC complementary and alternative medicine, 2024)
Post-stroke cognitive impairment (PSCI) not only increases patient mortality and disability, but also adversely affects motor function and the ability to perform routine daily activities. Current therapeutic approaches for, PSCI lack specificity, primarily relying on and medication and traditional cognitive therapy supplemented by a limited array of tools. Both transcranial direct current stimulation (tDCS) and virtual reality (VR) training have demonstrated efficacy in improving cognitive performance among PSCI patients. Previous findings across various conditions suggest that implementing a therapeutic protocol combining tDCS and VR (tDCS - VR) may yield superior in isolation. Despite this, to our knowledge, no clinical investigation combining tDCS and VR for PSCI rehabilitation has been conducted. Thus, the purpose of this study is to explore the effects of tDCS - VR on PSCI rehabilitation. This 4-week, single-center randomized clinical trial protocol will recruit 200 patients who were randomly assigned to one of four groups: Group A (tDCS + VR), Group B (tDCS + sham VR), Group C (sham tDCS + VR), Group D (sham tDCS + sham VR). All four groups will receive conventional cognitive rehabilitation training. The primary outcome measurement utilizes the Mini-Mental State Examination (MMSE). Secondary outcome measures include the Montreal Cognitive Assessment, Frontal Assessment Battery, Clock Drawing Test, Digital Span Test, Logic Memory Test, and Modified Barthel Index. Additionally, S-YYZ-01 apparatus for diagnosis and treating language disorders assesses subjects' speech function. Pre- and post-four-week intervention assessments are conducted for all outcome measures. Functional near-infrared spectroscopy (fNIRS) is employed to observe changes in oxygenated hemoglobin (HbO), deoxy-hemoglobin (HbR), and total hemoglobin (HbT) in the cerebral cortex. Our hypothesis posits that the tDCS - VR therapy, in opposed to individual tDCS or VR interventions, could enhance cognitive function, speech ability and daily living skills in PSCI patients while concurrently augmenting frontal cortical activity. This randomized study aims to provide a robust theoretical foundation supported by scientific evidence for the practical implementation of the tDCS - VR combination as a secure and efficient PSCI rehabilitation approach. Chictr.org.cn Identifier: ChiCTR2300070580. Registered on 17th April 2023.